PENINGKATAN KEMAMPUAN PENEMUAN SUMBER BAHAN PADA MATA KULIAH PENDIDIKAN KETERAMPILAN MELALUI PENDEKATAN INKUIRI - Florentina Widihastrini (Jurnal Kependidikan, 2009)
The aim of this study was to describe ways to improve methods of finding new materials existing in the environment for handicraft creation using the inquiry approach. The study was class action research involving 36 students in the third semester of PGSD UNNES. Data were collected by using observation, field notes, documentation, and interviews. The data were analyzed descriptively using the indicators that had been determined. The success level of the action included the level of students ability shown by results in material sources digging, creativity of making and creation, and learning process. Findings showed that, in the third cycle of the research, students ability of digging new material sources and their learning activity reached the good criteria level. Suggestions were given that the lecturer team (1) maximalize collaboration in identifying problems and deciding the alternative solutions and 2) use innovative learning activities to increase the quality of learning interaction.